Finger-guided Heller cardiomyotomy procedure to prevent the recurrence of esophageal achalasia in patients who are not qualified for laparoscopy: A case series - Handaya, Adeodatus Yuda (Int J Surg Case Rep, 2018)
INTRODUCTION: Achalasia is usually found in young adults with an incidence of 1 in 100,000 population. Symptoms include regurgitation, burning and substernal pain, weight loss, may also include a complete sense of fullness in the substernal region and persistent vomiting. The laparoscopy Heller cardiomyotomy and partial fundoplication have become the procedure of choice for surgical management of achalasia. PRESENTATION OF CASE: We report 6 cases, 4 males and 2 females with chief complaints were dysphagia. All patients displayed comorbidities. We performed a finger-guided Heller cardiomyotomy. All surgeries resulted in minimal intraoperative bleeding. Patients experienced neither leakage, postoperative fistula, dysphagia, nor postoperative reflux. One month after surgery, no patient experienced recurrence of their complaints. DISCUSSION: Since not all esophageal achalasia patients can undergo laparoscopy as the main treatment method due to some comorbidities, we did a modified technique of Finger-guided Heller cardiomyotomy to treat the patients. CONCLUSION: Finger-guided Heller cardiomyotomy for the treatment of esophageal achalasia in patients who are not qualified for laparoscopy due to comorbid factors can be considered to be an alternative treatment because the procedure is relatively easier, has fewer complications, and can prevent the recurrence of the disease.